Medicinal Plants Growing in Our Republic Medicinal Properties - Z.A.Yusupova; Sayramov Fayzullo Baratjon o`g`li; Mo`minjonova Zohidaxon Abduqunduzovna (Periodica Journal, 2023)
Medicinal plants growing in Uzbekistan in folk medicine its application, prevention of diseases occurring in the human body and treatment of them, as well as the role of medicinal plants in the pharmaceutical and perfume industry is incomparable. In addition, the role of medicinal plants and spices in the food industry is significant. In order to use medicinal plants in pharmaceuticals, it is necessary to increase the number of pharmaceutical factories in Uzbekistan and to produce the necessary medicine by using our medicinal plants. It is necessary to establish plantations for the purpose of rational use and protection of these medicinal plants, creation and breeding of many varieties
Keywords: sebarga; mint; fennel; coriander